2016
DOI: 10.4236/aim.2016.64030
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Five Expression Vectors for the Ha Gene in Constructing a DNA Vaccine for H6N2 Influenza Virus in Chickens

Abstract: A number of eukaryotic expression vectors have been developed for use as DNA vaccines. They showed varying abilities to initiate immune responses; however, there is little data to indicate which of these vectors will be the most useful and practical for DNA vaccines in different species. This report examines the use of five expression vectors with different promoters and Kozak sequence to express the same hemagglutinin (HA) protein of an H6N2 avian influenza virus for DNA vaccination in chickens. Although intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…In our previous report, the pCAG-HAk vaccine induced moderate antibody responses in SPF chickens (Shan et al, 2011), however, the same DNA vaccine did not induce measurable antibody in Hy-Line chickens (Shan et al, 2011). Furthermore, we found that even if other serological methods such as ELISA or western blot were used, no or very weak antibody responses were detected in the evaluation of the VR10102 vector vaccine expressing the same HA gene of H6N2 AIV (Shan et al, 2016). The reason for this is unknown but worth further investigation.…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…In our previous report, the pCAG-HAk vaccine induced moderate antibody responses in SPF chickens (Shan et al, 2011), however, the same DNA vaccine did not induce measurable antibody in Hy-Line chickens (Shan et al, 2011). Furthermore, we found that even if other serological methods such as ELISA or western blot were used, no or very weak antibody responses were detected in the evaluation of the VR10102 vector vaccine expressing the same HA gene of H6N2 AIV (Shan et al, 2016). The reason for this is unknown but worth further investigation.…”
Section: Discussionmentioning
confidence: 56%
“…However, incorporation of either chemical or genetic adjuvants to DNA vaccines modulates or enhances their efficacy (Cui & Mumper, 2003a). As our previous study demonstrated, lipofectin (liposome) was able to generate an enhanced DNA-induced immune response (Shan et al, 2016). In the present study, aluminum hydroxide (traditional adjuvant), Essai (microparticle) and Phema (nanoparticle) were assessed to see if the humoral immune response could be enhanced.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations